Current Approaches to the Management of Acute Thoracolumbar Disc Extrusion in Dogs - Moore, Sarah A.; Tipold, Andrea; Olby, Natasha J.; Stein, Veronica; Granger, Nicolas, Canine Spinal Cord Injury Consortium (CANSORT SCI); Moore, Sarah A.; Olby, Natasha J.; Gjessing, Kady M.; Davidson, Rhanna M.; Levine, Jonathan M.; McWhorter, Helen; et al. (Frontiers in Veterinary Science, 2020)
Intervertebral disc extrusion (IVDE) is one of the most common neurologic problems encountered in veterinary clinical practice. The purpose of this manuscript is to provide an overview of the literature related to treatment of acute canine thoracolumbar IVDE to help construct a framework for standard care of acute canine thoracolumbar IVDE where sufficient evidence exists and to highlight opportunities for future prospective veterinary clinical research useful to strengthen care recommendations in areas where evidence is low or non-existent. While there exist a number of gaps in the veterinary literature with respect to standards of care for dogs with acute thoracolumbar IVDE, recommendations for standard care can be made in some areas, particularly with respect to surgical decompression where the currently available evidence supports that surgery should be recommended for dogs with nonambulatory paraparesis or worse. While additional information is needed about the influence on timing of decompression on outcome in dogs that are deep pain negative for longer than 48 h duration, there is no evidence to support treatment of the 48 h time point as a cut off beyond which it becomes impossible for dogs to achieve locomotor recovery. Surgical decompression is best accomplished by either hemilaminectomy or mini-hemilaminectomy and fenestration of, at a minimum, the acutely ruptured disc. Adjacent discs easily accessed by way of the same approach should be considered for fenestration given the evidence that this substantially reduces future herniation at fenestrated sites. Currently available neuroprotective strategies such as high does MPSS and PEG are not recommended due to lack of demonstrated treatment effect in randomized controlled trials, although the role of anti-inflammatory steroids as a protective strategy against progressive myelomalacia and the question of whether anti-inflammatory steroids or NSAIDs provide superior medical therapy require further evaluation.